2007
DOI: 10.1016/j.vaccine.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent anthrax toxin display and delivery using bacteriophage T4

Abstract: We describe a multicomponent antigen display and delivery system using bacteriophage T4. Two dispensable outer capsid proteins, Hoc (highly antigenic outer capsid protein, 155 copies) and Soc (small outer capsid protein, 810 copies), decorate phage T4 capsid. These proteins bind to the symmetrically localized capsid sites, which appear following prohead assembly and expansion. We hypothesized that multiple antigens fused to Hoc can be displayed on the same capsid and such particles can elicit broad immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 35 publications
5
83
0
1
Order By: Relevance
“…However, when bulky antigens, such as the 88-kDa anthrax protective antigen, were fused to the N terminus of Hoc, there was no change in the affinity of Hoc binding to the capsid, whereas fusion of antigens to the C terminus caused a 13-to 400-fold decrease in affinity (40,41). This is consistent with the notion that the elongated structure of Hoc has its C-terminal domain bound to the capsid.…”
Section: Discussionsupporting
confidence: 81%
“…However, when bulky antigens, such as the 88-kDa anthrax protective antigen, were fused to the N terminus of Hoc, there was no change in the affinity of Hoc binding to the capsid, whereas fusion of antigens to the C terminus caused a 13-to 400-fold decrease in affinity (40,41). This is consistent with the notion that the elongated structure of Hoc has its C-terminal domain bound to the capsid.…”
Section: Discussionsupporting
confidence: 81%
“…Mice have proven historically to be difficult to protect with PA alone against a fully virulent challenge, despite stimulation in mice of high titres of toxin-neutralizing anti-PA antibody (Bielinska et al, 2007;Boyaka et al, 2003;Brossier et al, 2002;Flick-Smith et al, 2005;Hahn et al, 2006;Shivachandra et al, 2007;Welkos et al, 1989;Welkos & Friedlander, 1988;Williamson et al, 2005). In addition, our PA doses were purposefully selected to be suboptimal to increase the chances of revealing any antispore antibody contributions to protection.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has revealed that some DPA mutants are more potent in evoking an anti-PA host immunity response (2,6,51). On the other hand, an earlier study has shown that LFn, native LF, or catalytically inactive LF could augment the immunological response of PA-based vaccines against PA and enhance their immunoprotective efficiency, irrespective of whether immunization was carried out with DNA or protein (12,29,36,43,49). In this study, the chimera LFn-DPA still retained the function of each moiety.…”
Section: Discussionmentioning
confidence: 99%